PEMANFAATAN INSTAGRAM SEBAGAI TREND MEDIA PADA DAKWAH KAMPUS OLEH LDK SIMAHTUAH IAIN TEKENGON - nurliana jufrizal; Elis Mayanti Rambe; Ribi Yanti (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2022)
This study aims to find out the use of Instagram media for the development of da'wah by LDK Simahtuah IAIN Takengon and how effective the use of Instagram is as a medium of da'wah among adolescents. This research method is using descriptive qualitative method. The results obtained from this study are the many posts about religion uploaded on the LDK Simahtuah IAIN Takengon instagram page, so it is hoped that the da'wah carried out by LDK will also develop with the help of media in the form of Instagram. And the effectiveness of Instagram social media is considered effective because the followers of the LDK Smahtuah IAIN Takengon Instagram account are more than 1000 people so that many posts about da'wah are seen by their followers.